Inibição da metaloproteinase 2 por dois monômeros amplamente utilizados na formulação de adesivos dentinários - Carvalho, Rodrigo Varella de (2009)
The aim of this study was to evaluate the effect of different concentrations of 2-hydroxyethyl methacrylate (HEMA) triethyleneglycol dimethacrylate (TEGDMA) on the inhibition of matrix metalloproteinase 2 (MMP-2). Mouse gingival explants were cultured overnight in DMEM and the expression of secreted enzymes was analyzed by gelatin zymography in buffers containing 5 mM CaCl2 (Tris-CaCl2) in 50 mM Tris-HCl buffer with the addition of HEMA and TEGDMA at different concentrations (0.62, 1.25, 2.5 or 5.0% (v/v)). The gelatinolytic proteinase present in the conditioned media was characterized as matrix metalloproteinase by means of specific chemical inhibition with 0.5 mM of EDTA and 0.5 mM of NEM. The matrix metalloproteinases present in the conditioned media were characterized as MMP-2 by immunoprecipitation.The eletrophoretic bands were scanned and the transmittance values were analyzed with ImageJ software. Data was plotted and submitted to linear regression to investigate MMP-2 inhibition as a function of HEMA and TEGDMA concentration. Three major bands were detected in the zymographic assays. Those bands were characterized as MMP-2. Zymogene (72 kDa), intermediate (66 kDa) and active forms of MMP-2 (62 kDa) were inhibited by HEMA and TEGDMA in a dose-dependent way. These findings suggest that HEMA and TEGDMA could inhibit MMP-2 expression even at small concentrations.